Properly Folded Nonstructural Polyprotein Directs the Semliki Forest Virus Replication Complex to the Endosomal Compartment - Salonen, Anne (American Society for Microbiology, 2003)
The late RNA synthesis in alphavirus-infected cells, generating plus-strand RNAs, takes place on cytoplasmic vacuoles (CPVs), which are modified endosomes and lysosomes. The cytosolic surface of CPVs consists of regular membrane invaginations or spherules, which are the sites of RNA synthesis (P. Kujala, A. Ikäheimonen, N. Ehsani, H. Vihinen, P. Auvinen, and L. Kääriäinen J. Virol. 75:3873-3884, 2001). To understand how CPVs arise, we have expressed the individual Semliki Forest virus (SFV) nonstructural proteins nsP1 to nsP4 in different combinations, as well as their precursor polyprotein P1234 and its cleavage intermediates. A complex of nsPs was obtained from P123 or P1234, indicating that the precursor stage is essential for the assembly of the polymerase complex. To prevent the processing of the polyprotein and its cleavage intermediates, constructs with the mutation C478A (designated with a superscript CA) in the active site of the protease domain of nsP2 were used. Uncleaved polyproteins containing nsP1 were membrane bound and palmitoylated, and those containing nsP3 were phosphorylated, reflecting properties of authentic nsP1 and nsP3, respectively. Similarly, polyproteins containing nsP1 or nsP2 had enzymatic activities specific for the individual proteins, indicating that they were correctly folded in the precursor state. Uncleaved P12(CA) was localized almost exclusively to the plasma membrane and filopodia, like nsP1 alone, whereas P12(CA)3 and P12(CA)34 were found on cytoplasmic vesicles, some of which contained late endosomal markers. In immunoelectron microscopy these vesicles resembled CPVs in SFV-infected cells. Our results indicate that the nsP1 domain alone is responsible for the membrane association of the nonstructural polyprotein, whereas the nsP1 domain together with the nsP3 domain targets it to the intracellular vesicles.